Cardiac rehabilitation after percutaneous coronary intervention: Results from a nationwide survey. (March 2018) - Olsen, Siv JS; Schirmer, Henrik; Bønaa, Kaare H; Hanssen, Tove A
Aim: The purpose of this study was to estimate the proportion of Norwegian coronary heart disease patients participating in cardiac rehabilitation programmes after percutaneous coronary intervention, and to determine predictors of cardiac rehabilitation participation. Methods: Participants were patients enrolled in the Norwegian Coronary Stent Trial. We assessed cardiac rehabilitation participation in 9013 of these patients who had undergone their first percutaneous coronary intervention during 2008–2011. Of these, 7068 patients (82%) completed a self-administered questionnaire on cardiac rehabilitation participation within three years after their percutaneous coronary intervention. Results: Twenty-eight per cent of the participants reported engaging in cardiac rehabilitation. Participation rate differed among the four regional health authorities in Norway, varying from 20%–31%. Patients undergoing percutaneous coronary intervention for an acute coronary syndrome were more likely to participate in cardiac rehabilitation than patients with stable angina (odds ratio 3.2; 95% confidence interval 2.74–3.76). A multivariate statistical model revealed that men had a 28% lower probability ( p <0.001) of participating in cardiac rehabilitation, and the odds of attending cardiac rehabilitation decreased with increasing age ( p <0.001). Contributors to higher odds of cardiac rehabilitation participation were educational level >12 years (odds ratio 1.50; 95% confidence interval 1.32–1.71) and body mass index>25 (odds ratio 1.19; 95% confidence interval 1.05–1.36). Prior coronary artery bypass graft was associated with lower odds of cardiac rehabilitation participation (odds ratio 0.47; 95% confidence interval 0.32–0.70) Conclusion: The estimated cardiac rehabilitation participation rate among patients undergoing first-time percutaneous coronary intervention is low in Norway. The typical participant is young, overweight, well-educated, and had an acute coronary event. These results varied by geographical region.